STRATEGI GERAKAN SOSIAL BARU DALAM KAMPANYE PENGURANGAN SAMPAH PLASTIK DI BALI - Geraldine, Abraham; Azhar, Muhammad Ali; Noak, Piers Andreas (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2021)
ABSTRACT This research focuses on the strategy of the Pulau Plastik campaign in reducing plastic waste.This study produces descriptive data with a qualitative approach. Data obtained through interviews and document searches. The theory used is based on the Power In Movement by Sidney Tarrow, it was found that the results of this study show that the Pulau Plastik Campaign uses a strategic approach consisting of four components, namely: Support from the government in the form of a Governor Regulation as the basis for the movement, Community Screening, Advocacy, social media networks and songs as an effort to build public opinion on the issue of plastic waste. This strategy is carried out with the target of the government, society and business people so that the use of plastic in Bali is reduced and the community can switch to materials made from other materials that can be reused.   Keywords : Strategy, Campaign, Pulau Plastik.